Crystals : How to use them, how to wear them - Taylor, Ken Joules (Great Britain : Collins &Brown, 1999)
This comprehensive guide shows you how the power of crystals coan help enhance your living space, heal your body and realize your dreams. Inclusded are hundreds of practical tips and proyect ideas for harmonizing your home and garden, using crystal magic to attrace love and success, and waring your crystals as protectibve talismans.
Contenido The magic of crystals Crystals for the home Crystals for health Star crystals Crystals for personal power
Contiene General indez
Keywords: CRISTALES